Association between Cognitive Function and Depression with Human T-Cell Lymphotropic Virus 1 Seropositivity and Serointensity in UK Adults - Lance D. Erickson (MDPI AG, 2021)
Several viral, bacterial, and parasitic diseases have been associated with cognitive function and neuropsychiatric outcomes in humans, including human T-cell lymphotropic virus 1 (HTLV-1). In this study, we sought to further generalize previously reported associations of cognitive function and depression with HTLV-1 seropositivity and serointensity using a community-based sample of adults aged approximately 40 to 70 years (mean = 55.3 years) from the United Kingdom. In this sample, the results of adjusted linear regression models showed no associations of HTLV-1 seropositivity or serointensity with reasoning, pairs-matching, or reaction-time cognitive tasks or with depression. In addition, neither age, sex, educational attainment, nor income moderated associations of HTLV-1 seropositivity or serointensity with cognitive function or depression. In this middle-aged to older middle-aged adult community sample, HTLV-1 seropositivity and serointensity do not appear to be associated with reasoning, pairs-matching, and reaction-time tasks or with depression.